INTUMESCENT COATING INFLUENCE ON DRILLED HOLE INTEGRITY OF GLASS-CARBON HYBRID EPOXY COMPOSITE - KABIR, A K M SAROWER (2021)
Joining of materials using fasteners are commonly done by drilling and damage induced by drilling greatly affect the drilled hole quality